Photocatalytic proton reduction by a computationally identified, molecular hydrogen-bonded framework - Aitchison, Catherine M; Kane, Christopher M; McMahon, David P; Spackman, Peter R; Pulido, Angeles; Wang, Xiaoyan; Wilbraham, Liam; Chen, Linjiang; Clowes, Rob; Zwijnenburg, Martijn A; Sprick, Reiner Sebastian; Little, Marc A; et al. (Journal of materials chemistry. A, Materials for energy and sustainability, 2020)
We show that a hydrogen-bonded framework, TBAP -α, with extended π-stacked pyrene columns has a sacrificial photocatalytic hydrogen production rate of up to 3108 μmol g −1 h −1 . This is the highest activity reported for a molecular organic crystal. By comparison, a chemically-identical but amorphous sample of TBAP was 20-200 times less active, depending on the reaction conditions, showing unambiguously that crystal packing in molecular crystals can dictate photocatalytic activity. Crystal structure prediction (CSP) was used to predict the solid-state structure of TBAP and other functionalised, conformationally-flexible pyrene derivatives. Specifically, we show that energy-structure-function (ESF) maps can be used to identify molecules such as TBAP that are likely to form extended π-stacked columns in the solid state. This opens up a methodology for the a priori computational design of molecular organic photocatalysts and other energy-relevant materials, such as organic electronics. A hydrogen-bonded organic framework is an effective photocatalyst for producing hydrogen from water. Its crystal structure is key to its activity; a chemically identical, amorphous version is almost inactive, as rationalized by crystal structure prediction.